3x+3=6x-13

Simple and best practice solution for 3x+3=6x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3=6x-13 equation:



3x+3=6x-13
We move all terms to the left:
3x+3-(6x-13)=0
We get rid of parentheses
3x-6x+13+3=0
We add all the numbers together, and all the variables
-3x+16=0
We move all terms containing x to the left, all other terms to the right
-3x=-16
x=-16/-3
x=5+1/3

See similar equations:

| 10(-10x-6)=5(1-8x)-5 | | 6-1/4x=10 | | 5m+100=450 | | 5(v-4)-8=-2(-7+6)-3v | | -0.52z=-013 | | 1-x/13=5x/3 | | -8x40=-16 | | -3p-4p=-14 | | 3r+8=5r+10 | | 12*b=12.5 | | -6(1-6r=-2(r+3) | | 4k+7=32 | | 2/3n=12-2/3n | | 7+11=-3(4x-6) | | 5x-12(-3)=-6 | | 0.3x+0.4+0.5x=0.6x+.7 | | -0.52Xz=-013 | | 12=0.25a | | 2x-16+3x+20=180 | | R(p)=-4p^2+1950p | | 14x-13=4x=13 | | 1-j=7 | | 5(4x+7)=-36+31 | | 2x+4=25-2x+4 | | c4-10=2 | | 3x+4-x=-8 | | -8(2-x)-5x+10=-5x+1/3(45x+3) | | 2(f+1)+5=19 | | 4v+12=88 | | 7/6c+4=-10 | | 2x-7+6=x+7 | | y-1/3=1/9 |

Equations solver categories